SOCIAL CONFLICT IN THE FILM 1 BROTHER 7 NEPOKAN: A SOCIOLOGICAL STUDY OF ALAN SWINGEWOOD'S LITERATURE - Radiva Rezky Hermawan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
The article titled “Social Conflict in the Film 1 Kakak 7 Ponakan by Yandy Laurens: A Literary Sociology Analysis by Alan Swingewood” is a qualitative study using a descriptive approach that aims to describe the forms of social conflict found in the film 1 Kakak 7 Ponakan. This study focuses on three forms of social conflict: interpersonal conflict, intergroup conflict, and structural conflict experienced by the characters in the film. The primary data source for this study is the film 1 Kakak 7 Ponakan, analyzed through dialogue, character actions, and events that indicate the presence of social conflict, while supporting data sources include relevant books, articles, and journals. Data collection techniques were conducted through literature review and the watch-and-note technique, which involves repeatedly watching the film and noting the parts containing social conflict. Data analysis was carried out through the stages of identifying conflict scenes, classifying data based on the three forms of conflict, interpreting social relations between characters, and analysis using Alan Swingewood’s sociological theory of literature. The research findings indicate that interpersonal conflicts arise from differences in roles and responsibilities among family members; intergroup conflicts develop from clashes of interest between adult groups, children’s groups, and outsiders; and structural conflicts emerge due to the pressures of family circumstances and economic constraints that limit the characters’ life choices.